Report of the Managing Director to the International Monetary and Financial Committee on the IMF's Policy Agenda. (Policy Papers; Policy Paper ;, 2008)
This paper describes the policy changes that the Fund has made since the October 2007 IMFC meeting and the ways in which we plan to refocus the Fund's work to support our members more strongly. It also describes the steps that management, staff, and the Executive Board have agreed to put our own house in order-to reform our governance, contain our spending, and solve our income problem.